Neuro-pharmacological, analgesic and anti-inflammatory effects of crude extract of Cicuta virosa - Farah Saeed; Mansoor Ahmad; Meh jabeen; Noor Jahan; Syed Mehboob Alam (International Journal of Phytomedicine, 2014)
Cicutavirosa is commonly known as Water Hemlock and traditionally known as poisonous plants. In the present research work central nervous system (CNS), analgesic and anti-inflammatory effects were assessed in mice and rats. The crude extract showed anxiolytic response at 100 mg/kg which was evaluated through open field, head dip, light and dark, cage cross and swimming test. In open field (73.33±3.28) and light and dark test (time spent in light 5.16±1.07 min.) the movements of mice were increased as compare to standard drugs, whereas in forced swimming test (FST) themean forced mobility was reduced to 1.16±0.02 seconds. At the dose of 500mg/kg of C. virosa, CNS inhibition was observed in cage cross test and dip cage activity. The results of locomotor and exploratory activity were also found reduced in comparison to control and standard Diazepam (2 mg/kg-1). Analgesic activity was evaluated by acetic acid and formalin method. The abdominal constrictions were observed. C. virosa at the dose of 50 mg/kg exhibited maximum inhibition of writhes, in first phase (57.67%) second (3.26%) and third phase (0%). The results of analgesic activity was compared with aspirin (orally administered, 300 mg/kg). C. virosaalso significantly inhibited formalin induced licking and biting response at the dose of 50mg/kg. Anti-inflammatory effect was observed by carrageenan induced edema at 300 and 500 mg/kg doses of C. virosa. Maximum inhibition of edema was observed at 500mg/kg (23.07%). The results of neuropharmacological, analgesic and anti-inflammatory activities of C. virosawere found significant at P ≤ 0.05.